2011
DOI: 10.1117/12.883185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface chemistry on the quality factors of micromechanical resonators

Abstract: Single monolayers of molecules were found to strongly affect the quality factors of MHz-range torsional silicon resonators. By changing a single monolayer of molecules on the surface of a 5-µm-wide, 250-nm-thick silicon resonator less than 0.07% of the total mass the quality factor of the resonator was increased by 70%. In contrast, the standard commercial coating, a thin layer of silicon oxide, dissipates at least 75% of the mechanical energy in similarly sized resonators. Since the relative importance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Although it is possible to remove the oxide layer by annealing to 800°C in ultra-high vacuum (UHV) [18,19] or using chemical etching, the oxidefree silicon surface is unstable in air, and the oxide layer regrows within minutes under ambient atmosphere [12]. In a series of investigations, Henry, Hines and coworkers found that some permanent improvement in the mechanical quality factor is possible by monolayer coating of the surface with alkanes [20][21][22]. It is, however, unknown whether these improvements extend to low temperatures, where many of the most sensitive measurements are carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to remove the oxide layer by annealing to 800°C in ultra-high vacuum (UHV) [18,19] or using chemical etching, the oxidefree silicon surface is unstable in air, and the oxide layer regrows within minutes under ambient atmosphere [12]. In a series of investigations, Henry, Hines and coworkers found that some permanent improvement in the mechanical quality factor is possible by monolayer coating of the surface with alkanes [20][21][22]. It is, however, unknown whether these improvements extend to low temperatures, where many of the most sensitive measurements are carried out.…”
Section: Introductionmentioning
confidence: 99%